Titanium isotopic evidence for a shared genetic heritage of refractory inclusions from different carbonaceous chondrites. (1st June 2019) - Render, Jan; Ebert, Samuel; Burkhardt, Christoph; Kleine, Thorsten; Brennecka, Gregory A.
Abstract: Insights into the earliest stages of our Solar System can be derived from its oldest dated solids, calcium-aluminum-rich inclusions (CAIs). In particular, investigating isotopic anomalies of nucleosynthetic origin in CAIs offers potential clues to the genetic heritage of refractory inclusions and the reservoir(s) involved in their formation. To this point, however, nucleosynthetic anomalies in refractory inclusions have almost exclusively been recognized in (1) relatively large CAIs from CV3 chondrites, employing chemical purification and high-precision mass spectrometry, or (2) from sub-mm-sized hibonite-rich objects ( e.g., PLACs, SHIBs) from the Murchison CM2 chondrite using much less precise in-situ techniques. Whereas the latter have been shown to be highly anomalous in their isotopic compositions, their genetic connection to 'regular' CAIs from carbonaceous chondrites remains poorly understood. Here, we aim to address this issue by taking advantage of a new technique that allows for high-precision analysis of sub-mm-sized inclusions. Using this method, we report Ti isotope anomalies in a suite of twelve CAIs from five different CO carbonaceous chondrites, as well as ten refractory inclusions from the CM2 chondrite Jbilet Winselwan using MC-ICPMS. We find that these CO and CM CAIs exhibit Ti isotopic compositions very similar to those of previously investigated CV3 (and of two CK3) CAIs, suggesting a fundamental genetic relationship of CAIs found within these chondrite groups. As such, our data indicates that CAIs from various groups of carbonaceous chondrites formed from similar matter and in a single region of the solar nebula ( i.e., derived from a single common CAI-formation region). Collectively, these data show evidence of large-scale transport of CAIs over a significant range of heliocentric distances, covering at least the accretion areas of the CV, CK, CO, and CM chondrites. In addition, we report two inclusions consisting of hibonite-rich crystal aggregates from Jbilet Winselwan that exhibit highly irregular nucleosynthetic Ti signatures, implying a distinct origin from the aforementioned CAIs. These inclusions may represent an earlier generation of refractory material, perhaps more akin to the previously mentioned PLACs and/or SHIBs.